Left ventricular mechanics in idiopathic dilated cardiomyopathy: systolic-diastolic coupling and torsion - Meluzín, Jaroslav; Špinarová, Lenka; Hude, Petr; Krejčí, Jan; Poloczková, Hana; Podroužková, Helena; Pešl, Martin; Orban, Marek; Dušek, Ladislav; Kořínek, Josef (Journal of the American Society of Echocardiography, 2009)
BACKGROUND: In idiopathic dilated cardiomyopathy (IDC), myocardial deformational parameters and their mutual relationships remain incompletely characterized. METHODS: Thirty-seven patients with IDC underwent two-dimensional speckle-tracking echocardiography (2D-STE) to assess left ventricular rotation, torsion, and longitudinal, circumferential, and radial systolic and diastolic strains and strain rates. Additionally, 2D-STE was performed in 14 controls. RESULTS: All deformational parameters on 2D-STE were significantly lower in patients with IDC compared with controls. Seven patients exhibited opposite basal (positive, counterclockwise) and 11 patients exhibited opposite apical (negative, clockwise) rotation at end-systole. Circumferential, radial, and longitudinal early diastolic strain rates were correlated most strongly with the corresponding spatial components of systolic deformation. CONCLUSION: In patients IDC, all torsional, systolic, and diastolic deformational parameters were decreased. Corresponding three-dimensional components of systolic and diastolic deformations were closely coupled. Considerable variation in the direction of basal and apical rotation exists in a subset of patients with IDC.
Keywords: dopplerovská echokardiografie; Echocardiography, Doppler; lidé; Cardiomyopathy, Dilated; dilatační kardiomyopatie; torzní deformity; mužské pohlaví; Female; Elasticity Imaging Techniques; Torsion Abnormality; Adult; Ventricular Dysfunction, Left; Male; ženské pohlaví; dospělí; Humans; lidé středního věku; Middle Aged; dysfunkce levé srdeční komory; elastografie